MATH 307 ASSIGNMENT 7, SPRING 2013 SOLUTIONS

6.4 Assume a, b, n ∈ N. Suppose that gcd(a, b) = 1. Prove that gcd(na, nb) = n. Proof. Let d = gcd(na, nb). Since n|na and n|nb, we know n ≤ d. On the other hand, since gcd(a, b) = 1, we know there exist x, y ∈ Z with ax + by = 1 (Corollary 10.4.5). Thus (na)x +(nb)y = n, which implies d|n (Theorem 11.1.6), which implies d ≤ n. Hence d = n as desired.

6.5 Let n ∈ N. What is the list of pairs produced when the Euclidean Algorithm is applied to the input (5n, 2n) ? Solution. Here’s the algorithm: Input: (5n, 2n) (2n, n) (n, 0). Output: gcd(5n, 2n) = n 5n − 2(2n) = n, 2n − 2n = 0,

Answer: (5n, 2n), (2n, n), (n, 0).

6.7 Claim 1. 61 is not an integer combination of 9 and 15. Proof. 3|9 and 3|15, so 3 divides any integer combination of 9 and 15. Since 3 61, it follows that 61 is not an integer combination of 9 and 15. Claim 2. 61 is an integer combination of 9 and 16. Proof. 61 = 16 + 5(9).

98) (98. 126 − 98 = 28. 126) (126. 126) = 14 Now we read the algorithm backwards to write 14 as an integer combination of 126 and 224: 14 = 98 − 3(28) = 98 − 3[126 − 98] = −3(126) + 4(98) = −3(126) + 4[224 − 126] = 4(224) − 7(126) 14 = 4(224) − 7(126) 224 − 126 = 98. 13) (13. 78 − 65 = 13. Solution.6. Output: gcd(224. use the Euclidean Algorithm to compute the greatest common divisor. 221 − 2(78) = 65. 28) (28. Output: gcd(299. Solution. . 98 − 3(28) = 14. 221) = 13 Now we read the algorithm backwards to write 13 as an integer combination of 221 and 299: 13 = 78 − 65 = 78 − [221 − 2(78)] = −221 + 3(78) = −221 + 3[299 − 221] = 3(299) − 4(221) 13 = 3(299) − 4(221) 299 − 221 = 78. (a) 126 and 224.8 For each pair below. Here’s the Euclidean Algorithm: Input: (224. 221) (221. (b) 221 and 299. 78) (78. 0). 28 − 2(14) = 0. 0). 65 − 5(13) = 0. Here’s the Euclidean Algorithm: Input: (299. 65) (65. and express the greatest common divisor as an integer combination of the two numbers. 14) (14.

Since 6|60 and 6|42.1. the entire solution set is {(−600 + 13k. By Theorem 11.6. we can write 1 as an integer combination of 7 and 5. By Theorem 11. 93 − 7k ) : k ∈ Z}.9 For each diophantine equation below. Since 6 104.4. since gcd(7. y ) = (6. −15) is one solution. . Now. we can write 1 as an integer combination of 17 and 13.4. 13) = 1. (b) 21x + 15y = 93 Solution. 15) to get the following equivalent diophantine equation: 7x + 5y = 31. or using the Euclidean algorithm you can find one such integer combination. the entire solution set is {(6 + 11k. or using the Euclidean algorithm you can find one such integer combination. we divide by 3 = gcd(21. since gcd(28. −15 − 28k ) : k ∈ Z}. or using the Euclidean algorithm you can find 1 = 17(−3) + 13(4). if any exist. y ) = (−62. First off. Hence (x. Now. 800 − 17k ) : k ∈ Z}. Hence (x. say 1 = 28(2) + 11(−5). 93) is one solution. Hence (x. Multiply by 3 to get 3 = 28(6) + 11(−15). Multiply by 200 to get 200 = 17(−600) + 13(800). 5) = 1. (d) 588x + 231y = 63 Solution. 11) = 1. it follows that 6|(60x +42y ) whenever x. say 1 = 7(−2) + 5(3). By Theorem 11. 231) to get the following equivalent diophantine equation: 28x + 11y = 3. the entire solution set is {(−62 + 5k. First divide by 21 = gcd(588. there are no integers x and y with 60x + 42y = 104. y ) = (−600. (a) 17x + 13y = 200 Solution. By either guessing. find all solutions.1. Since gcd(17. By (probably) guessing. 800) is one solution. y ∈ Z. Multiply by 31 to get 31 = 7(−62) + 5(93). we can write 1 as an integer combination of 28 and 11.4.1. By guessing. (c) 60x + 42y = 104 Solution.

which implies d ≤ d. a − b) = gcd(2a. Hence. Proof. Proof. 2b). (Contrapositive) Assume n is not prime. b ∈ Z. which implies d ≤ d . then 4n − 1 = 3 which is divisible by 3. we have the following factorization: b−1 2n − 1 = (2a )b − 1 = (2a − 1) (2a 1)|(2n k=0 a 2 − 2ak . Proof. Since d |(a + b) and d |(2b). a n which shows that 2 − 1 is a nontrivial divisor of 2 − 1. If n = 1. and assume 6|(k 3 + 5k ). Claim 2. which shows − − 1). Since d |(2a) and d |(a − b). 3 divides 4n − 1 for every positive integer n. by Lemma 6. using the inductive hypothesis. so that 4k = 3m + 1. 2b). 6. which shows 3|(4k+1 − 1). b ∈ N such that 1 < a. and d = gcd(a + b. 2a − (a − b) = a + b. Fix an integer k ≥ 1.3. Thus 4k+1 − 1 = 4 · 4k − 1 = 4(3m + 1) − 1 = 4(3m) + 3 = 3(4m + 1).17 Let a. If n = 1. a − b). Notice (k + 1)3 + 5(k + 1) = k 3 + 3k 2 + 3k + 1 + 5k + 5 = (k 3 + 5k ) + 3k (k + 1) + 6. . which implies 6|3k (k + 1). we know d divides their sum (a + b) + (a − b) = 2a. which implies d ≤ d . b < n and n = ab.39 Let n ∈ N. 1 < 1 < 2n − 1 (since 1 < a < n). Then 4k − 1 = 3m for some m ∈ Z. Thus 2n − 1 is not prime. Hence. Prove that if 2n − 1 is prime. then n is prime. Moreover. a − b) = gcd(a + b. we know d divides their difference (a + b) − 2b = a − b. 6 divides n3 + 5n for every positive integer n. Let d = gcd(a + b.24 Claim 1. we know 2 divides either k or k + 1. Then there exist a.6. Hence d is a common divisor of a + b and a − b. 2|k (k + 1). Hence d is a common divisor of 2b and a + b. Since d|(a + b) and d|(a − b). Hence. Inductive step. ( ) Since one of k and k + 1 must be even. and assume 3|(4k − 1). Proof. Fix an integer k ≥ 1. 6. Thus 6 divides (k + 1)3 + 5(k + 1). (Induct on n) Base case. a − b). Inductive step. we know d divides the following integer combinations: 2a − 2(a − b) = 2b. d = gcd(2a. we see that 6 divides each of the three terms on the right side of ( ). To show d = d = d it suffices to verify the three inequalities d ≤ d ≤ d ≤ d. Hence d is a common divisor of 2a and a − b. (Induct on n) Base case. Prove that gcd(a + b.4. then n3 + 5n = 6 which is divisible by 6.

Claim 1. we know there exist primes p0 . Claim 4. Notice ak+1 − 2 = 22 k+1 n − 1 = (22 + 1)(22 − 1) = ak (ak − 2). . There are infinitely many primes. Hence the first log2 (log2 (N )) numbers in the list a0 . Since d also divides am . p2 . Throw in the prime 2. Proof. k k Hence ak and ak − 2 both divide ak+1 − 2. are all less than or equal to N . Claim 3. p3 . d must divide the difference am − (am − 2) = 2. but I’m adding one to the solutions anyway. Finally. so the statement “If n < m. this implies ak and all an with n < k divide ak+1 − 2. a2 . by Claim 1. Hence d ∈ {±1. (Induct on m) Base case. gcd(am . . 22 ∈ Z) k <N k < log2 (log2 (N )). . Fix an integer N > 2. This implies that the corresponding log2 (log2 (N )) prime factors p0 . Remark. then there are no nonnegative integers strictly less than m. . these primes are distinct. and assume d is a common divisor of an and am . Fix and integer k ≥ 0 and assume an |(ak − 2) whenever n < k . and we have found at least log2 (log2 (N )) primes strictly less than N . an divides am − 2 whenever n < m. . p1 . which implies d|(am − 2). Then. a1 . By Claim 2. Inductive step. an ) = 1 as desired.41 Let an = 22 + 1 for all integers n ≥ 0.6. an divides ak+1 − 2 whenever n < k + 1. . . p1 . You were not asked to prove the following claim in your homework. then an |(am − 2)” is vacuously true. First. Proof. an and am are relatively prime whenever n = m. since n n an = 22 + 1 = 2(22 −1 ) + 1 is odd. By the inductive hypothesis. (found in the proof of Claim 3) are also less than or equal to N . it follows that d = 2. Since an > 1 whenever n ≥ 0. Claim 2. p2 . Proof. Without loss of generality we may assume n < m. we know an |(am − 2). ±2}. notice ak ≤ N ⇔ ⇔ ⇔ 22 + 1 ≤ N 2 2k k (definition of ak ) (since N. There are at least log2 (log2 (N )) prime numbers less than N . If m = 0. In other words. which is not one of the pn ’s (since each ai is odd). Proof. with pn |an for each n ≥ 0. Thus ak and all the factors of ak − 2 divide ak+1 − 2. . . Let m and n be distinct nonnegative integers. Hence. .

(b) ∀m. n ∈ Z : gcd(2m + n. m − n) ≤ gcd(3n. m − n). 3m) as desired. it follows that d divides the following integer combinations: 3n = (2m + n) − 2(m − n). d ≤ gcd(3n. Answer: False Proof. Set d = gcd(2m + n. m − n) = gcd(5. 3m). Then gcd(2m + n. and prove your assertion. n ∈ Z : gcd(2m + n. 6) = gcd(3n. Hence. 1) = 1 ≥ 3 = gcd(3.I. For a counterexample. 3m = (2m + n) + (m − n). 3m). let m = 2 and n = 1. Answer: True Proof. 3m). Determine the truth value of the following statements. m − n) ≥ gcd(3n. Since d|(2m + n) and d|(m − n). (a) ∀m. .